Odpowiedzi

2010-02-08T15:55:31+01:00
3/7 - 5/8x = 1/7
-5,8x = -2/7
x= 16/35

0,9x-17=19
0,9x=36
x=40

11=0,2x
x= 55

3(x-6)=18
3x-18=18
3x=36
x=12

1/2y + 6 = y-4
10=1/2y
y=5

x- 1/3 = 0
x=1/3

1/2x - 1=29
1/2x = 30
x=15
Najlepsza Odpowiedź!
2010-02-08T15:59:40+01:00
3/7 - 5/8 x= 1/7
-5/8x=1/7-3/7
-5/8x=-2/7
x=-16/35


0,9x-17=19
0,9x=19+17
0,9x=36
x=40


11=0,2x
-0,2x=-11
x=55


3(x-6)=18
3x-18=18
3x=18+18
3x=36
x=12


1/2y+6=y-4
1/2y-y=-4-6
-0,5y=-10
y=20


x-1/3=0
x=1/3


1/2x-1=29
1/2x=29+1
1/2x=30
x=60